Potential strategies for the management of drug-resistant tuberculosis. (September 2020) - Sharma, Divakar; Sharma, Sandeep; Sharma, Juhi
Highlights: Emergence of DR-TB is the consequence of the failure of theranostic approaches. Alternative approaches should be used singly/combination against the resistance. Combinatorial approaches could be a long-term solution for combating AMR. Abstract: In the current scenario, the emergence of drug resistance in Mycobacterium tuberculosis is the consequence of the failure of conventional diagnostic and treatment approaches. To combat this global emergence of drug resistance, alternative approaches such as pathogen-centric (use of repurposed drugs, novel analogues of existing anti-TB drugs and novel compounds with a different mechanism of action), host-centric (immunomodulatory agents, therapeutic vaccines, immune and cellular therapies) and nano-based drug/vaccine delivery should be used singly or in combination. Diverse types of nano-carriers have assessed as auspicious diagnostic and drug delivery systems. In this focused review, we have suggested a long-term solution for combating antimicrobial resistance and also an attractive means to increase patient compliance and reduce treatment duration.